2021
DOI: 10.1101/2021.04.26.21256110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for long covid in previously hospitalised children using the ISARIC Global follow-up protocol: A prospective cohort study

Abstract: Background The long-term sequelae of coronavirus disease 2019 (Covid-19) in children remain poorly characterised. This study aimed to assess long-term outcomes in children previously hospitalised with Covid-19 and associated risk factors. Methods This is a prospective cohort study of children (18 years old and younger) admitted with confirmed Covid-19 to Z.A. Bashlyaeva Children's Municipal Clinical Hospital in Moscow, Russia. Children admitted to the hospital during the first wave of the pandemic, between Ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(100 citation statements)
references
References 28 publications
3
94
0
3
Order By: Relevance
“…IP address: 44.224.250.200, on 30 Aug 2021 at 02:24:36, subject to the Cambridge Core terms of use, available at recovery, 8 bringing up a type of Covid-19 infection referred to as long Covid or Post-Covid-19 syndrome. 9 This case can also be seen among children 10 , as supported by a pediatric cohort study done in Russia, in which fatigue, sleep disturbance, sensory, gastrointestinal, dermatological, neurological, respiratory, cardiovascular, and musculoskeletal problems were observed in children with Covid-19 in the long term 19 . Our findings were also in line with these, as shown in Figure 2, evoking long Covid in our study group.…”
Section: Discussionmentioning
confidence: 80%
“…IP address: 44.224.250.200, on 30 Aug 2021 at 02:24:36, subject to the Cambridge Core terms of use, available at recovery, 8 bringing up a type of Covid-19 infection referred to as long Covid or Post-Covid-19 syndrome. 9 This case can also be seen among children 10 , as supported by a pediatric cohort study done in Russia, in which fatigue, sleep disturbance, sensory, gastrointestinal, dermatological, neurological, respiratory, cardiovascular, and musculoskeletal problems were observed in children with Covid-19 in the long term 19 . Our findings were also in line with these, as shown in Figure 2, evoking long Covid in our study group.…”
Section: Discussionmentioning
confidence: 80%
“…The vast majority of these studies focused solely on adults [3][4][5][6][7]. Results of these studies are heterogenous, due to large methodological differences with regard to study design, data sources, data collection modes, and the definition of health outcomes [3,4,[8][9][10]. Clinical studies of patients hospitalized for COVID-19 have consistently reported that high proportions of patients continue to suffer from one or more health complaints for months after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms frequently observed include fatigue, weakness, muscle pain, sleep disorders, depressive symptoms, dizziness, lack of memory and concentration, and shortness of breath. This has been observed mainly among adults [8,9,11], whereas evidence on pediatric populations is still very limited [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…4 Generally, the estimated prevalence of persistent symptoms in children with SARS-CoV-2 infection presenting in secondary care have been higher, ranging from 8% to 25% 3-7 months after infection onset. 5 6 We estimated the prevalence of persistent symptoms reported in children during the summer, autumn and winter of 2020-2021, and their association with SARS-CoV-2 infection, in a large household-based community cohort study.…”
Section: Introductionmentioning
confidence: 99%